If you take a mouse to school - Numeroff, Laura Joffe; Bond, Felicia (New York : Laura Geringer Books/HarperCollins Publishers, 2002)
Follows a boy and his mouse through a busy day at school.
Keywords: Schools -- Fiction; Mice -- Juvenile fiction